2020
DOI: 10.1063/5.0010844
|View full text |Cite
|
Sign up to set email alerts
|

Carbon doping of GaN: Proof of the formation of electrically active tri-carbon defects

Abstract: Carbon doping is used to obtain semi-insulating GaN crystals. If the carbon doping concentration exceeds 5×10 17 cm -3 , the carbon atoms increasingly form triatomic clusters. The tri-carbon defect structure is unambiguously proven by the isotope effect on the defects' local vibrational modes (LVMs) originally found in samples containing carbon of natural isotopic composition (~99% 12 C, ~1% 13 C) at 1679 cm -1 and 1718 cm -1 . Number, spectral positions, and intensities of the LVMs for samples enriched with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In particular, two absorption peaks at 1679 and 1718 cm −1 have been reported as observed in highly C-doped GaN and AlN. 28,29) Since the peak positions were consistent with the reports, they could be considered to originate from the tricarbon complexes of C N -C Ga -C N (basal), which consist only of C N -C Ga bonds nearly perpendicular to the c-axis, and C N -C Ga -C N (axial), which consist of the C N -C Ga bond parallel to the c-axis, respectively. 30) Figure 3 shows the detailed atomic configurations for tri-carbon complexes.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In particular, two absorption peaks at 1679 and 1718 cm −1 have been reported as observed in highly C-doped GaN and AlN. 28,29) Since the peak positions were consistent with the reports, they could be considered to originate from the tricarbon complexes of C N -C Ga -C N (basal), which consist only of C N -C Ga bonds nearly perpendicular to the c-axis, and C N -C Ga -C N (axial), which consist of the C N -C Ga bond parallel to the c-axis, respectively. 30) Figure 3 shows the detailed atomic configurations for tri-carbon complexes.…”
Section: Resultsmentioning
confidence: 93%
“…29) On the other hand, the C Ga -C N -C Ga complexes vibrate at frequencies very close to the LVMs at 1679 and 1718 cm −1 , and are formed close to the C N -C Ga -C N complexes. 28) So far, the tri-carbon defects C N -C Ga -C N are abundant due to the strong reflection intensity in highly C-doped GaN. However, as shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…[43,119] A detailed analysis of the isotope effect on the LVMs in crystals with 13 C-enriched doping clearly proved the assignment of those modes to complexes involving three C atoms. [120] Based on their polarization behavior, those LVMs were proposed to be related to crystallographically inequivalent configurations of C N À C Ga,off À C N (C Ga,off denotes an off-center Ga site). [120] Furthermore, the intensity of these complex-related LVMs was sensitive to additional illumination with light of 385 nm (3.22 eV), indicating the presence of related charge state transition levels in the GaN bandgap.…”
Section: Sub-bandgap Excited Luminescence Rl C : Multicarbon Complexesmentioning
confidence: 99%
“…[120] Based on their polarization behavior, those LVMs were proposed to be related to crystallographically inequivalent configurations of C N À C Ga,off À C N (C Ga,off denotes an off-center Ga site). [120] Furthermore, the intensity of these complex-related LVMs was sensitive to additional illumination with light of 385 nm (3.22 eV), indicating the presence of related charge state transition levels in the GaN bandgap. This is further supported by the observation of an absorption onset at 2.5-2.6 eV resulting in a bulk photovoltaic effect in surface photovoltage (SPV) measurements [121] and a PL band around 1.62 eV in those samples, [93] for clarity further referred to as RL C .…”
Section: Sub-bandgap Excited Luminescence Rl C : Multicarbon Complexesmentioning
confidence: 99%
“…Especially, Matsubara et al, 30) demonstrated that the concentration of V N + is comparable to that of C N in heavily C doped GaN when the concentrations of O, Si, and H are low. Additionally, when C concentration exceeds its solid solubility during growth, C atoms would tend to exist in the form of C N + (rather than C N -), or substitute Ga site to form C Ga instead, or form C related complexes such as tricarbon C N -C Ga -C N , [31][32][33] which could act as donors and have been theoretically investigated in literatures. 8,31,34) Therefore, combining with the main influence of the above two aspects, high concentration of compensation donors leads to the reverse shift of the Fermi level upward to the conduction band.…”
mentioning
confidence: 99%